A INFLUÊNCIA DO TURISMO NAS PRINCIPAIS CIDADES DA MICRORREGIÃO DA BODOQUENA (BONITO/MS, BODOQUENA/MS, BELA VISTA/MS, JARDIM/MS, NIOAQUE/MS). - Crespo, Joelma; Souza, Eulália; Fernandes, Dandara; Aquino, Armando (ANAIS DO ENIC, 2018)
-